Explaining the Exchange Rate Pass-Through in Different Prices - Faruqee, Hamid (IMF Working Papers; Working Paper ;, 2002)
This paper examines the performance of different new open economy macroeconomic models in explaining the exchange rate pass-through in a wide range of prices. Quantitative versions of different models are used to derive the dynamic response of various prices to an exchange rate shock. Predicted responses are compared with the evidence based on VAR models to examine how well different models fit the data. The results show that the best-fitting model incorporates a number of features highlighted by different strands of the literature: sticky prices, sticky wages, distribution costs, and a combination of local and producer currency pricing.